Analysis of 4C's Ability in the Implementation of Online Learning in Elementary Schools - Helda Kusuma Wardani; Suhartono Suhartono (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2022)
The goal of this study was to describe the 4 C's ability to implement the 2020/2021 odd semester learning at Jitu State Elementary School in Sidoarjo Regency. The research location, which is included in the countryside, is intended to obtain a qualitative picture of the ability of the 4 C's in elementary schools, most of which are rural. Qualitative research with a descriptive narrative research design is applied. The result is that during this pandemic, there is a reality that online learning does not allow the realization of the collaborative abilities of all classes. Critical thinking skills, creative thinking, and communication are planned and implemented in learning. The ability of students who study under the guidance of their parents at home decreases compared to face-to-face learning. The teacher marks the existence of student work that parents do. Individual learning causes a decline in students' critical thinking, creative thinking, and verbal communicative skills, although the three skills (creative thinking, critical thinking, and communication) are still visible in students. The impact of learning with individual assignments on students shows a significant decrease in the 4 C's ability. Keywords: 4 C's, learning, critical thinking, creative thinking, elementary school ==================================================Tujuan dari penelitian ini adalah mendeskripsikan kemampuan 4 C’s dalam pelaksanaan pembelajaran semester ganjil 2020/2021 Sekolah Dasar Negeri Jitu Kabupaten Sidoarjo. Lokasi penelitian yang termasuk pedesaan dimaksudkan agar diperoleh gambaran kualitatif dari kemampuan 4 C’s di Sekolah Dasar yang mayoritas ada di daerah pedesaan. Penelitian kualitatif dengan desain penelitian naratif deskriptif diterapkan. Hasilnya pada masa pandemic ini ada realita bahwa pembelajaran dalam jaringan tidak memungkinkan diwujudkannya aspek kemampuan kolaboratif semua kelas. Aspek kemampuan berpikir kritis, berpikir kreatif, dan komunikasi terencana dan terlaksana dalam pembelajaran. Kemampuan siswa yang belajar dibimbing orangtua di rumah menurun dibanding saat pembelajaran tatap muka. Guru menandai adanya pekerjaan siswa yang dikerjakan orangtua. Pembelajaran individual menyebabkan menurunnya keterampilan berpikir kritis, keterampilan berpikir kreatif, dan keterampilan komunikatif verbal siswa, walaupun ketiga keterampilan (berpikir kreatif, berpikir kritis, komunikasi) masih terlihat pada diri siswa. Dampak pembelajaran dengan penugasan individual pada diri siswa menampakkan penurunan kemampuan 4 C’s sigifikan. Kata kunci: 4 C's, learning, critical thinking, creative thinking, sekolah dasar